Investigation of machining parameters for the multiple response optimization of micro electrodischarge milling - Mehfuz, Reyad; Ali, Mohammad Yeakub (Springer, 2009)
This paper investigated the influence of three micro electrodischarge milling process parameters, which were feed rate, capacitance, and voltage. The response variables were average surface roughness (Ra), maximum peak-to-valley roughness height (Ry), tool wear ratio (TWR), and material removal rate (MRR). Statistical models of these output responses were developed using three-level full factorial design of experiment. The developed models were used for multiple-response optimization by desirability function approach to obtain minimum Ra, Ry, TWR, and maximum MRR. Maximum desirability was found to be 88%. The optimized values of Ra, Ry, TWR, and MRR were 0.04, 0.34 μm, 0.044, and 0.08 mg min−1, respectively for 4.79 μm s−1 feed rate, 0.1 nF capacitance, and 80 V voltage. Optimized machining parameters were used in verification experiments, where the responses were found very close to the predicted values.